THE SOURCE OF INFECTION AND THE MOST FREQUENT CAUSES OF REACTIVE ARTHRITIS IN KOSOVO - Lahu, Ali (Mater Sociomed, 2016)
INTRODUCTION: Reactive arthritis is an autoimmune condition which emerges as a counteraction towards an infection which has a focus elsewhere in the body. The purpose of this study is isolation of causative agents of reactive arthritis and ascertains the source of infection. The study has been carried out in the Rheumatology Clinic in Prishtina and specialized ambulance O.S. “Vendenisi-AL” in Besiana, whereas isolation of causative agents has been carried out in the National Institute for Public Health (NIPH). The study has prospective, comparative and analytical feature. RESULTS: Out of 100 patients, 66% were males and 34% females. Among males we have noticed domination of post-urethritis and post-streptococcic reactive arthritis, whereas among females dominates reactive arthritis of enteral etiology. The study concludes that: urogenital tract was the source of infection with 66% of cases, nasopharyngeal tract with 19% of cases, and enteral tract with 15% of cases respectively. Predominantly presents bacteria are E. Coli with 21%, Staphylococcus aureus with 20%, Streptococcus B. hem. gr. A with 16% of cases respectively and other species. CONCLUSION: frequency of arthritis with urogenital etiology was 2:1 in favor of males, with nasopharyngeal etiology 3:1 in favor of males, whereas in arthritis with enteral etiology we have noticed a slight dominance in favor of females.